2006
DOI: 10.1111/j.1365-3059.2006.01443.x
|View full text |Cite
|
Sign up to set email alerts
|

Volatile metabolite profiling to detect and discriminate stem‐end rot and anthracnose diseases of mango fruits

Abstract: The volatile metabolites from the headspace gas of containerised mango ( Mangifera indica ) cv. Tommy Atkins fruits, surface wounded and inoculated with the two fungal anamorphic pathogens Colletotrichum gloeosporioides and Lasiodiplodia theobromae , or non-inoculated (controls), were profiled using a portable gas chromatograph/mass spectrometer to discriminate diseases of mango. Thirty-four compounds were detected relatively consistently among replicates. Several of these were disease/inoculation-discriminato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…These techniques permit high temporal resolution, but only limited resolution of analytes due either to a lack of mass spectral information (zNose®) or a lack of chromatographic separation and ion fragmentation (PTR-MS). Although these shortcomings may be partially ameliorated in new handheld GC-MS devices (Müller et al , 2005; Moalemiyan et al , 2006; Bednar et al , 2011), the need to transport, maintain, and provide power for such expensive, sensitive equipment in the field complicates their adoption. Furthermore, near-real-time analysis requires rapid chromatography, which cannot separate components of complex samples (Gaquerel and Baldwin, 2013); or may not include chromatography at all.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques permit high temporal resolution, but only limited resolution of analytes due either to a lack of mass spectral information (zNose®) or a lack of chromatographic separation and ion fragmentation (PTR-MS). Although these shortcomings may be partially ameliorated in new handheld GC-MS devices (Müller et al , 2005; Moalemiyan et al , 2006; Bednar et al , 2011), the need to transport, maintain, and provide power for such expensive, sensitive equipment in the field complicates their adoption. Furthermore, near-real-time analysis requires rapid chromatography, which cannot separate components of complex samples (Gaquerel and Baldwin, 2013); or may not include chromatography at all.…”
Section: Introductionmentioning
confidence: 99%
“…1-Pentanol and ethyl boronate were also reported to be unique for bacterial soft rot of carrot (Vikram et al, 2006). Similarly, in one (1)-pentanol and ethyl boronate, were detected in L. theobromae inoculated mangoes alone, while thujol was observed only in C. gloeosporioides inoculated mangoes (Moalemiyan et al, 2006). Acetyl hydrazide, propylcarbamate, propenyl bromide, acetone, 1-ethenyl-4-ethyl benzene, thiirane and 1-(methylthio)-E-1-propene were unique to onion bulbs artificially inoculated with Botrytis allii, while 3-bromo furan was specific to bulbs inoculated with E. carotovora subsp.…”
Section: Discussionmentioning
confidence: 89%
“… Beck et al (2015) showed that this method could differentiate between damaged and healthy Centaurea solstitialis in the natural environment. Portable GC-MS could efficiently discriminate between stem rot and anthracnose diseases of mango using 1-pentanol and ethyl boronate as marker volatiles for stem rot and thujol as a marker of anthracnose ( Moalemiyan et al, 2006 ). Aksenov et al (2014) coupled differential mobility spectrometry (DMS) with GC to detect citrus greening disease in plants at early stages of disease development.…”
Section: Non-invasive Diagnosis Of Diseased Plants By Volatile Analysmentioning
confidence: 99%